Anti-Inflammatory and Analgesic Effect from Decoction of Itchy Leaves (Laportea decumana (Roxb.) Wedd.) - Khairani, Sondang; Rika Sari Dewi; Yeshika Krispansis Maelissa (Faculty of Pharmacy Universitas Pancasila, 2024)
Itchy leaves have the ability as analgesics, anti-inflammatory, asthma, antimalaria and antihypertension. Empirically in Maluku and Papua, itchy leaves are used topically to treat pain and inflammation. This study aims to examine the antiinflammatory and analgetic effects orally of an Itchy leaves decoction. Anti-inflammatory testing using the Winter method, rats were divided 5 groups negative control given aquadest, positive control given sodium diclofenac 1.8 mg/200 g BW rats, the test group given an infusion of itchy leaves dose 0.3 g/Kg BW (I), 0.6 g/Kg BW (I) and 1.2 g/Kg BW (III). Analgesics testing using Siegmund method, mice were divided 5 groups, negative control given aquadest, positive control given sodium diclofenac 0.26 mg/20 g BW mice, the test group given decoction of itchy leaves dose 0.4 g/Kg BW (I), 0.8 g/Kg BW (II) and 1.6 g/Kg BW (III). Results of Mann-whitney test, infusion of itchy leaves had a significant anti-inflammatory and analgesic effect on the negative control group, p value <0.05. Precentage of positive control edema inhibition and the test group dosage I, II, III was obtained by 27.94%; 15.97%; 25.89%; and 26.86%, percentage inhibition of positive control and the test group dosage I, II, III was obtained by 59.42%; 43.93%; 45.70% and 80.22%. Itchy leaves decoction has a lower anti-inflammatory effect than diclofenac sodium. The analgesics effect of decoction of Itchy leaves at doses of 0.4 g/Kg BW and 0.8 g/Kg BW was lower, dose of 1.6 g/Kg BW was higher than diclofenac sodium.